REVERSE CURRENCY WARS IN LIGHT OF INTERNATIONAL CONFLICTS AN ANALYTICAL VISION - Arshad Abdul Latif Turki (Scholar Express Journals, 2023)
The global economy is living after Covid-19 at the end of 2019 and the beginning of the Russian-Ukrainian conflict on February 24, 2022, over which more than a year has passed. Political and financial variables have accumulated instability and reinforced global inflation. In conjunction with these variables, the US Federal Reserve decided to raise the interest rate through Successive several steps that may extend until the middle of this year, which led to a significant increase in the value of the dollar while not decreasing its value in the coming period in light of the Russian-Ukrainian conflict and the US sanctions package on both the Russian money and energy files. The leading currencies and their stability are the basis on which it is based. The stability of the global economic system is why it receives wide attention from developed and developing countries and international institutions to ensure that it is not exposed to severe fluctuations and neutralizes inflationary pressures globally. In emerging and developing countries, the contemporary form of currency wars will create instability for uncle Lat and the prices of food and raw materials. The research considers a primary goal based on showing the reality of the leading currencies and the global monetary system in light of Covid-19 and the subsequent financial rescue packages and economic sanctions in light of the Russian-Ukrainian conflict. The research reached several results, most notably the state of inflation experienced by the global economy, especially after the closure of China and the Russian war. Ukraine and Russia, and the countries of the European Union had the largest share of the rise in inflation rates, in addition to the trend by Russia and its allies to find financial transactions away from the dollar in light of the restriction by the Swift system, according to IMF data, 86 out of 109 developing countries witnessed a rise in inflation. Prices of food commodities over 12 months, at an average of (5%), the share of developing countries was (79%) compared to (27%) for developing countries that are more immune to the rise in food commodity prices
Keywords: Reverse currency war; quantitative easing; trade deficit; inflationary pressures